Discriminating different‐purpose burrows of the North American badger Taxidea taxus. Issue 1 (16th May 2019) - Symes, Stephen A.; Klafki, Richard; Packham, Roger; Larsen, Karl W.
Abstract : For many species, burrowing is used for a variety of purposes, such as finding food, sheltering from elements and predators, or raising offspring. For threatened species, differentiating among burrow types allows effective conservation efforts, and provides insight into habitat attributes needed at different stages in their life‐history. This study investigated whether burrow characteristics for the North American badger Taxidea taxus allowed discrimination among summer, winter and natal burrows, and whether these characteristics reflected different requirements by the animals. Radio‐telemetry was used to monitor badgers and classify burrows based on seasonal occupancy. Characteristics relating to thermal and security cover, along with features that could correlate with prolonged usage, were measured across winter, natal and summer burrows. Winter and natal burrows showed greater vegetation cover than summer burrows, potentially indicating increased thermal protection and predator avoidance. However, for winter burrows, greater vegetation cover did not translate into warmer, winter subterranean temperatures compared to summer burrows. Winter and natal burrows also had larger soil fans and, in the case of natal burrows, also had more entrances than summer burrows. These features may be indicative of prolonged usage. All told, it appeared summer burrows were distinguishable from winter and natal burrows based on the dimensions and construction of the burrow, location and surrounding vegetation. However, because badgers are capable of modifying their environment (including existing burrows) it is difficult to make precise predictions of where certain burrow types will occur. Still, the results of this study allow protection efforts or other management considerations to be apportioned more effectively among different burrow types. Comparable work is needed in other regions to understand how burrow characteristics spatially vary in importance.